Microhabitat preferences of Biomphalaria pfeifferi and Lymnaea natalensis in a natural and a man-made habitat in Southeastern Tanzania - Jürg Utzinger; Marcel Tanner (Memorias do Instituto Oswaldo Cruz, 2000)
Schistosoma mansoni is an important human parasitic disease which is widespread throughout Africa. As Biomphalaria pfeifferi snails act as intermediate host, knowledge of their population ecology is an essential prerequisite towards understanding disease transmission. We conducted a field study and assessed the density and microhabitat preferences of B.pfeifferi in a natural habitat which was a residual pool of a river. Repeated removal collecting revealed a density of 26.6 [95% confidence interval (CI): 24.9-28.3] snails/m2. B.pfeifferi showed microhabitat preferences for shallow water (depths: 0-4cm). They were found most abundantly close to the shoreline (distances: 0-40cm), and preferred either plant detritus or bedrock as substratum. Lymnaea natalensis, a snail which may act as a host for human Fasciola gigantica, also occurred in this habitat with a density of 34.0 (95% CI: 24.7-43.3) snails/m2, and preferred significantly different microhabitats when compared to B.pfeifferi. Microhabitat selection by these snail species was also investigated in a man-made habitat nearby, which consisted of a flat layer of concrete fixed on the riverbed, covered by algae. Here, B.pfeifferi showed no preference for locations close to the shoreline, probably because the habitat had a uniform depth. We conclude that repeated removal collecting in shallow habitats provides reliable estimates of snail densities and that habitat changes through constructions may create favourable microhabitats and contribute to additional disease transmission.